Is insurance instability associated with hypertension outcomes and does this vary by race/ethnicity?. - Kressin, Nancy R.; Terrin, Norma.; Hanchate, Amresh D.; Price, Lori Lyn.; Moreno-Koehler, Alejandro.; LeClair, Amy.; Suzukida, Jillian.; Kher, Sucharita.; Freund, Karen M. (Tufts University. Tisch Library., 2020)
Keywords: Insurance, Health, Health status disparity, Hypertension.; Springer Open.